Assessment of seismic risk of Nan Theun 2 hydroelectric power dam in Lao P.D.R. - Thammavong, Souvanaly (2012)
Lao PDR depends mainly on dams to produce electricity by hydropower from surface flow to meet the electricity consumption demand of the country. Moreover, the construction and maintenance of hydroelectric power facilities help the country attain its goal to be a key power exporter in ASEAN in order to improve the country's socioeconomic profile. Currently, the Nam Theun 2 hydroelectricity power dam is the largest power dam with a capacity of 1070 MW, which is one of main income sources of the country. It is located in one of the tributaries of the Mekong river, the Theun river - a place tha is vital in maintaining a full biodiversity of many wild animals and plants in this part of the significant national protected area. This solid concrete gravity dam maintains its stability against design loads from the geometric shape, mass and strength of the concrete. In this study, the seismic risk profile of the Nam Theun 2 dam was assessed based on the seismic risk profile recommended in Laos. The dam stability and stress conditions were analyzed by using two-dimensional finite element method for varying horizontal earthquake acceleration from 0.05-0.20g corresponding to the three seismic zones in Laos. According to the analyses of the different scenarios, the von Mises stresses developed at the critical sections of the dam were within the permissible stress of the material. Thus, its was concluded that the Nam Theun 2 hydropower dam would be adequate to resist horizontal earthquakes with accelerations less than 0.20g.